2019
DOI: 10.1007/s11600-019-00285-3
|View full text |Cite
|
Sign up to set email alerts
|

A multifaceted analysis of the relationship between daily temperature of river water and air

Abstract: The aim of the study was to establish the strength and direction of the relationship between daily temperature of river water and air with the use of selected estimation methods. The relationship was assessed for the River Noteć and its tributaries (Western Poland), using the cross-correlation function and Granger causality. The study established cause-and-effect relations for "water-air" and "air-water" directions of influence. It was confirmed that forecasting the pattern of flowing water temperature from ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…The temperature of river water constitutes an important element of the hydrological regime, being subjected to daily, seasonal, annual, and multi-annual change [1]. Seasonal changes are the consequence of the influence of climatic factors predominant in a given geographical zone, whereas multi-annual changes may additionally point to the impact of local factors, also anthropogenic [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature of river water constitutes an important element of the hydrological regime, being subjected to daily, seasonal, annual, and multi-annual change [1]. Seasonal changes are the consequence of the influence of climatic factors predominant in a given geographical zone, whereas multi-annual changes may additionally point to the impact of local factors, also anthropogenic [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…High correlations between annual and monthly air and river water temperature values have been demonstrated for various regions, among others in the United States and Canada [16,[20][21][22][23][24], in Asia and Eurasia [25][26][27][28], and in Europe [29][30][31][32][33][34][35][36]. Studies concerning the thermal regime of Polish rivers have also confirmed the existence of significant relations and the impact of air temperature on the variability of river water temperature [4,5,13,[37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal changes in water temperature were generally closely related to the air temperature pattern [75,76]; however, the results should be treated with caution due to the clear diurnal water temperature dynamics observed in rivers and streams [77] which the grab sampling method does not take into account. Nevertheless, attention could be paid to the Da ńków stream (site T5), which was characterized by a lower annual temperature range compared to other sites.…”
Section: Relationships Between Precipitation and Biogenic Concentrations And Between Chemical Compoundsmentioning
confidence: 87%
“…Yu (2019) suggests that direct measurements of air-water thermal flux can only be carried out for limited or local locations. Graf (2019) suggests that the analysis of the relationship between irradiation and thermal storage in water must be carried out in detail both spatially and temporally. For ecosystem analysis and utilization of coastal waters and lakes resources, detailed local scale information is needed, resulting from in situ measurements (Shinoda et al, 2019).…”
Section: Discussionmentioning
confidence: 99%